Svolta ambientale, istituzionalizzazione e valorizzazione nella gestione dei beni comuni nei contesti fluviali e alpini dell’Italia settentrionale (xii-xiii secolo) - Riccardo Rao (Mélanges de la Casa de Velázquez)
This paper focuses on the management of the commons between the 12th and 13th centuries in three areas of great importance for the environmental resources in Northern Italy: the Sesia and Po river area near Vercelli and the alpine areas of Valle d’Aosta and Valtellina. The aim is to demonstrate that the strong environmental pressure on commons did not imply their disappearance, but rather their transformation and enhancement. The creation of institutions and statutes for their governance, as well as the adoption of new forms of management, based on investitures and indirect management, made this change possible.